Pengaruh Penambahan Sargassum sp. pada Pakan Terhadap Kecerahan Warna Ikan Cupang (Betta sp.) - Leony Aplonia Vianney Rubu; Agnette Tjendanawangi; Ridwan Tobuku (Jurnal Aquatik, 2026)
This study was conducted to evaluate the effect of incorporating Sargassum sp. flour into feed on the color enhancement, absolute growth, and survival rate of Betta sp.. The experiment lasted for 60 days and employed a Completely Randomized Design (CRD) consisting of four treatments: a control group (without Sargassum sp. supplementation), treatment A (10%), treatment B (20%), and treatment C (30%), with each treatment replicated three times. The observed parameters included color brightness, absolute growth, survival rate, and water quality. The findings revealed that the inclusion of Sargassum sp. flour significantly influenced (P < 0.05) both color brightness and absolute growth of Betta fish. The most effective treatment was recorded at the 20% supplementation level, producing the highest color brightness score of 4.50 ± 0.10, indicating a very high level of pigmentation. In addition, the survival rate across all treatments remained at 100%, demonstrating that the use of Sargassum sp. flour is safe at inclusion levels of up to 30%. Therefore, the incorporation of 20% Sargassum sp. flour in feed can be considered an effective strategy to enhance the color quality of Betta fish without negatively affecting their survival. Keywords: Absolute growth, betta fish (Betta sp.), color brightness, feed formulation, Sargassum sp., survival rate